Peningkatan Produktivitas Kelompok Petani Kelapa Desa Batu Lungun Melalui Pembuatan Alat Pengupas Kelapa Sederhana - Defelinu Harefa; Muhammad Khairul Amri Rosa (Universitas Bengkulu, 2021)
The use of traditional coconut peelers by the farmers is found to be less efficient and effective as well as less safe. Therefore, as a community service activities in the KKN of University of Bengkulu Period 93, a Unib’s student had implemented the knowledge gained in college in order to benefit to the community, especially in Bengkulu Province. In this KKN activity, the design and manufacture of a simple coconut peeler was carried out to be used by people in Desa Batu Lungun, Kecamatan Nasal, Kaur Regency, Bengkulu Province, in where many people work as coconut farmers. The stages of designing process include interviews about community needs and continued with designing and manufacturing a simple coconut peeler. The tool-making process includes forming, welding, and finishing. After running a proper testing of the tools, socialization was done to provide an explanation to the public about the functions and benefits, working principles, how to use, and maintainance of the tools. The product that had been finished are handed over to be used by the community. In addition, we also explain how to make the tools so that people can make their own if they need more. The result obtained from this activity is that the coconut peeler designed and made by students participating in KKN Period 93 can help the Batu Lungun village community, especially coconut farmers, in peeling coconuts from their gardens more efficiently and more safely. By using this tool, the process of peeling 1 coconut takes an average of 15 seconds.